2021
DOI: 10.1177/17446295211022124
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of training methods to increase staff’s knowledge and implementation of positive behaviour support in residential and day settings for individuals with intellectual and developmental disabilities

Abstract: Behaviour support plans (BSPs), if accurately implemented, have been found to increase skills and decrease challenging behaviour of individuals with intellectual and developmental disabilities. Training is essential for staff to acquire the skills necessary for accurate implementation. The aim of this systematic literature review was to evaluate procedures used to train staff in Positive Behaviour Support (PBS), on both knowledge of PBS and implementation of BSPs. Systematic searches of 4 databases identified … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 44 publications
1
14
0
Order By: Relevance
“…A strength of our study was that it showed that it is possible to include complete teams of direct staff members and their supervising psychologist to participate in a well manualised PBS training that teaches ABA techniques on a level that fits the background and educational level of direct staff. This is in accordance with the results of a recent systematic review on the effectiveness of PBS staff training components (Mahon et al, 2022), which showed the importance of description in combination with feedback, and non-technical language for direct staff members. Yet, some limitations of our study should be noted.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…A strength of our study was that it showed that it is possible to include complete teams of direct staff members and their supervising psychologist to participate in a well manualised PBS training that teaches ABA techniques on a level that fits the background and educational level of direct staff. This is in accordance with the results of a recent systematic review on the effectiveness of PBS staff training components (Mahon et al, 2022), which showed the importance of description in combination with feedback, and non-technical language for direct staff members. Yet, some limitations of our study should be noted.…”
Section: Discussionsupporting
confidence: 91%
“…A systematic review of mainly small and uncontrolled studies found some evidence that training staff in PBS indeed might reduce challenging behaviours in individuals with intellectual disabilities (MacDonald & McGill, 2013), but effects on quality of life were not reported. Moreover, the limited research on direct staff provided PBS often focused on staff outcomes, rather than on outcomes regarding the individuals with intellectual disabilities and challenging behaviours themselves (MacDonald & McGill, 2013; Mahon et al, 2022). Given that the primary objective of PBS is to reduce challenging behaviours and increase the quality of life of individuals with intellectual disabilities, more research on the effects of staff‐provided PBS on these outcomes is necessary.…”
Section: Introductionmentioning
confidence: 99%
“…Despite this finding, some research has found that feedback appears to be the most commonly applied BST component (Brady et al, 2019;Mahon et al, 2021). Importantly, discrepancies related to feedback type, amount, form (e.g., written, verbal, in situ), and latency (e.g., immediate or delayed) have been observed across studies, which could influence service provider outcomes (i.e., dependent variable; Mahon et al, 2021), and the resultant conclusions drawn.…”
Section: Training Approaches and Associated Researchmentioning
confidence: 99%
“…Further, providing training in situ may improve training outcomes (Knotter et al, 2018; Mullins & Scott, 2022; van Oorsouw et al, 2009). However, there are some gaps in the literature related to feedback type discrepancies and its use in isolation or alongside other components (Mahon et al, 2021; van Oorsouw et al, 2009). Further, although service user reductions in challenging behaviours and increased quality of life should be considered the ultimate training outcome, these variables have often been omitted in the past (Cox et al, 2015; Gormley et al, 2019; MacDonald & McGill, 2013; van Oorsouw et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation